Mongolian Spots – A challenging clinical sign. (October 2021) - Kolbe, V.; Boy, D.; Büttner, A.
Highlights: Mongolian Spots are the most common birthmarks in newborns. Extensive MS can be associated with inborn errors of metabolism. It can be challenging to distinguish between MS and hematomas. MS should be well documented to avoid false accusations. Abstract: Mongolian Spots (MS) are the most common birthmarks in newborn children. The condition presents as greenish-bluish to greyish macules, particularly in the lumbosacral area. The incidents of MS can vary in different ethnic groups and normally fade in early childhood. MS can be misinterpreted as hematomas because of the color and the predilection site. This paper discusses the case of a two-month old female admitted to hospital under suspicion of child abuse. The clinical forensic examination of the infant and her two older sisters found the children were in good health and did not show signs of abuse, despite the infant presenting with multiple and extensive greyish-blue macules. Thirteen months later, a welfare officer requested another forensic examination on the now 15-month-old child after noticing greyish-blue macules. Following a second examination, no evidence of abuse was found. This case illustrates the issue of MS as a differential diagnosis of hematomas.